Impact of induced joy on literacy in children: does the nature of the task make a difference?. Issue 3 (3rd April 2017) - Tornare, Elise; Cuisinier, Frédérique; Czajkowski, Nikolai O.; Pons, Francisco
ABSTRACT: This research examined whether induced joy influences fifth graders' performance in literacy tasks. Children were asked to recall a joyful experience, used as a joy induction, before completing either a grammar (Study 1) or textual comprehension task (Study 2). The grammar task involved understanding at the surface level and retrieval of appropriate declarative and procedural knowledge, but limited elaboration unlike the textual comprehension task, which tackled inference generation. By differentiating tasks based on depth of processing required for completion we aimed at testing the validity of two concurrent hypotheses: that of a facilitating effect and that of a detrimental effect of induced joy. Compared to controls, joy induced children showed better performance on the grammar task – specifically children with lower language ability. No differences across groups emerged as a function of joy induction on the text comprehension task. Results are discussed with respect to emotion effects on cognition.